Political Marketing of Stream by Candidates through Facebook in the 2018 Regional Election of East Java - Arina Rohmatul Hidayah (Politicon : Jurnal Ilmu Politik, 2021)
Previous researches on political marketing found several gaps in terms of content and essence as a process of political exchange and interaction. Based on this, the researcher aims to actualize the essence of the basic theory or concept of political marketing into the 2018 regional election of East Java through the use of social media as an interactive media. For the content aspect, researcher selected political stream as a society cultural system. It considered as one of the determining aspects for voter preferences, especially in East Java.  Qualitative approach with the content analysis method conducted for this research by applying political marketing theories and the political stream concepts from Clifford Geertz. The result of this research revealed that political stream also revolves around the political elite. Each candidate tries to display some stream characteristics that are considered familiar by the public to increase redundancy or message certainty. In this case, Gus Ipul-Puti is considered to be stronger and more varied than Khofifah-Emil. However, from public reaction, not all of the political streams conveyed can be clearly captured by the users. This occurred because there are some cultural differences between the message sender and it’s receiver. Nevertheless, the implications of this research can be used as a benchmark of how to utilize political stream effectively in order to get a positive response from the public. Then, it also can be literacy medium to recognize the cultural symbols raised in political contestation in Indonesia.